Root-shoot ratio and SOD activity are associated with the sensitivity of common bean seedlings to NaCl salinization - García, Marina (2024)
The response of two common bean (Phaseolus vulgaris) varieties with different sensitivities to salinity (Montalbán: sensitive; I-193: moderately sensitive) was studied to determine some phytometric and physiological characteristics that could be associated with their differential sensitivities. Plants were sown in a greenhouse during the seedling stage and irrigated with a nutrient solution to which NaCl of 60 mol m−3 was added, while a control group was maintained in parallel. In Montalban, salinity caused a significant reduction in root biomass while shoot biomass and leaf area decreased with salt stress in both genotypes. The root/shoot ratio slightly increased in I.193 and decreased in Montalban salinized plants. Chlorophyll content increased with salinity in both genotypes. The presence of O2·- (superoxide radicle) in root apex decreased under the saline condition which did not occur in the case of H2O2. Superoxide dismutase (SOD) activity increased in roots and primary leaves under salt stress to a greater extent in I-193 than in Montalban. Four SOD isoenzymes were detected, one MnSOD, one FeSOD, and two Cu/ZnSOD, but their expression varied according to the variety. Catalase (CAT) activity increased only in the roots of stressed Montalban plants. These results suggest that root/shoot ratio and SOD enzyme activity are related to the lower salt sensitivity shown by I-193.